Journal Overlap of the GEOBASE Database with the GeoRef and Web of Science Databases. Issue 1 (17th August 2020) - Kimball, Rusty
ABSTRACT: A journal overlap analysis was performed between the GEOBASE database and the GeoRef and Web of Science databases, respectively. This overlap analysis determined that there are 480 serial titles common to both GEOBASE and GeoRef with 23% of the GEOBASE journals indexed in GeoRef. Further, there are 710 serial titles common to both GEOBASE and Web of Science with 34% of the GEOBASE journals indexed in Web of Science. These overlap results may be significant in collection budgetary decisions. The method presented for conducting the overlap of serials lists is fast and easily replicated, thus potentially beneficial to academic libraries.